History of an eel life: part 2. The colonization of European and African continental waters - (:unkn) unknown (My University, 1992)
Close to the European and African coastline, the metomorphosis is going on and the leptocephalic larvae is transformed into a civelle. Thanks to its transparency, the observer can make out the heart, the liver, the brain, the gills, the spine and the digestive tract.
Keywords: African Research